Sejarah pendidikan Islam : napaktilas perubahan konsep, filsafat, dan metodologi pendidikan Islam dari era nabi SAW sampai ulama Nusantara - Ramayulis (Jakarta : Kalam Mulia, 2012)
History of Islamic education in Indonesia.
Includes bibliographical references (p. 451-464).
Keywords: Islamic education -- Indonesia; Islamic religious education -- Indonesia; Islamic education -- History; Islamic religious education -- History